PROBLEM OF COST CONCEPTS AND CLASSIFICATION OF COSTS - Sánchez Barraza, Bernardo Javier (2009)
Actually, in economic and business many companies and institutions have the problem of choosing the appropiate classification of costs, wich let them cost theirs products and services reliably. This work wants to explain and clarify concepts of costing and gives examples about real companies and costing procedures through formulas. Also, this work should let the readers choose the sort classification of costs most advantageous to the reality or line of business in wich these work.